ตัวชี้วัดผลลัพธ์การพยาบาลข้ามวัฒนธรรม - ชฎารัตน์ ครุตศุทธิพิพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purpose of this research was to identify transcultural nursing outcome indicators by using Delphi technique. The participants were 18 experts who has been working related to care transcultural patient. The selected experts were from variance fields including nurse administrators, quality nurse, nursing instructor with transcultural experience and registered nurses who provide care for foreign patient. There are 3 steps in the Delphi technique. First, all experts were asked to identify transcultural nursing outcome indicators by using semi open-ended questionnaire. Second, the data received from the first stage was analyzed and develop to the rating scale questionnaires. Third, the answered questionnaires were reanalyzed. Then, the questionnaires were sent back to the expert to confirm their answers. After reconfirming process, all data was analyzed by using mean and interquartile range to summarize transcultural nursing outcome indicators. The results shown that transcultural nursing outcome indicators composed of 36 items: 30 items were evaluated as the most essential items and 6 items were essential items. The items can be classified into 5 domains as follows: 1) Patient Safety in transcultural nursing 2 items 2) Satisfaction in transcultural nursing service 11 items 3) The knowledge and understanding of health matter in transcultural nursing 7 items 4) Healthcare based on culture, belief and treatment 11 items and 5) Transcultural nursing to alleviate the suffering 5 items.